Implementasi Sistem Manajemen Pembelajaran Daring Berbasis Moodle dengan Microserver On-Premises di Sekolah Binekas - Nasution, Surya Michrandi; Septiawan, Reza Rendian; Ruriawan, Muhammad Faris (Institut Riset dan Publikasi Indonesia (IRPI), 2024)
Hybrid learning is a learning method that is increasingly being adopted in the post-pandemic era. Hybrid learning requires infrastructure that supports online learning that can be carried out freely and independently by students. Currently, Sekolah Binekas, as one of the well-known private schools in South Bandung area, still does not have an effective learning management system (LMS) infrastructure. To overcome this problem, a learning management system can be implemented using a microserver located at Sekolah Binekas (on-premises). Due to the current number of students that is not too large, for now, the server specifications required are not too high, so the microserver is still sufficient for current needs. The LMS used is Moodle which is commonly used. The activities done this time can help Sekolah Binekas to carry out hybrid learning for its students which can ultimately improve the quality of the students produced. Based on the results of the post-implementation survey, the results showed that, in general, Sekolah Binekas as a partner in this community service activity, were satisfied and hoped that similar activities could be carried out in the future. In the future, next activities that can be done could be activities that related with the implementation of the LMS at Binekas School, such as training of the LMS usage for teaching staffs, as well as activities to upgrade the LMS infrastructure to support better learning activities.